2023
DOI: 10.1101/2023.06.20.545784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body mass and growth rates predict protein intake across animals

Abstract: Organisms require dietary macronutrients in specific ratios to maximize performance, and variation in macronutrient requirements plays a central role in niche determination. Although it is well-recognized that development and body size can have strong and predictable effects on many aspects of organismal function, we lack a predictive understanding of ontogenetic or scaling effects on macronutrient intake. We determined protein and carbohydrate intake throughout development on lab populations of locusts and te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Grasshoppers tend to be tight regulators, and a given population will consistently select the same ratio. Most studies have measured ITs in finalinstar juveniles or adult grasshoppers and show interspecific variation spanning from the most protein-biased 1p:0.6c ratio (Melanoplus femurrubrum) (9) to the most carbohydrate-biased 1p:2.5c ratio (Schistocerca cancellata) (130). There can even be substantial variation within a genus.…”
Section: Carbohydrate Eatenmentioning
confidence: 99%
See 3 more Smart Citations
“…Grasshoppers tend to be tight regulators, and a given population will consistently select the same ratio. Most studies have measured ITs in finalinstar juveniles or adult grasshoppers and show interspecific variation spanning from the most protein-biased 1p:0.6c ratio (Melanoplus femurrubrum) (9) to the most carbohydrate-biased 1p:2.5c ratio (Schistocerca cancellata) (130). There can even be substantial variation within a genus.…”
Section: Carbohydrate Eatenmentioning
confidence: 99%
“…For all consumers, protein is the main building block for growing tissues, and carbohydrates (and/or lipids) are the primary energy fuel. Vertebrate studies suggest that protein requirements are generally higher in early ontogeny, matching higher specific growth rates (for a review, see 130). A study of South American locusts (S. cancellata) measuring ITs for each developmental stage from hatchlings to adults demonstrated that mass-specific protein intake decreases in a predictable way with development and decreased growth rate, representing a fourfold decrease…”
Section: Carbohydrate Eatenmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative nutrition has long been recognised as a powerful approach to uncover how nutritional needs have evolved (Baker & Czarnecki‐Maulden, 1991 ; Mitchell, 1962 ; Payne & Wheeler, 1968 ). It was used to provide insights into the effects of both macro‐ and micronutrients on health (see Baker & Czarnecki‐Maulden, 1991 ; Lei et al., 2022 , references therein), including the effects of protein on morphological and reproductive traits (Swanson et al., 2016 ; Talal et al., 2023 ). Comparative nutrition studies are few because it is difficult to obtain a single dataset that maps the effects of specific nutrients to life‐history traits, such as lifespan or reproduction.…”
mentioning
confidence: 99%